2012
DOI: 10.1177/0886260512469110
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Examination of Factors Influencing Men’s Engagement in Intimate Partner Violence Groups

Abstract: This article examines the findings of an ecological analysis of the factors influencing men's engagement in intimate partner violence (IPV) groups. Individual interviews and two focus groups were conducted with men who participated in group programs in two agencies in Canada. Our qualitative analysis of interviews and focus groups suggested that both individual and program-related factors were determinants in the men's engagement. These findings drew our attention to the influence of certain factors outside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
(51 reference statements)
0
15
1
1
Order By: Relevance
“…In fact, three of four men who dropped out identified the theme "hearing other men's stories as motivation to change." This suggests dropouts may experience early treatment similar to completers but that environmental factors, that is, lack of outside supports, limit the impact of engagement in treatment for them as Roy et al (2013) suggested. To address this issue facilitators could routinely check for environmental challenges, that is, problems with transportation, housing, that could then be problem solved in the group.…”
Section: Samplementioning
confidence: 85%
See 2 more Smart Citations
“…In fact, three of four men who dropped out identified the theme "hearing other men's stories as motivation to change." This suggests dropouts may experience early treatment similar to completers but that environmental factors, that is, lack of outside supports, limit the impact of engagement in treatment for them as Roy et al (2013) suggested. To address this issue facilitators could routinely check for environmental challenges, that is, problems with transportation, housing, that could then be problem solved in the group.…”
Section: Samplementioning
confidence: 85%
“…Brownlee and Chlebovec (2004) found a similar theme with men who had completed treatment. Roy et al (2013) identified personal motivation prompted by the recognition of a problem and wanting to improve their lives as a key factor in engagement in domestic abuse treatment. Contrino et al (2007) link increase engagement through active learning of skills with greater recall of program curriculum at treatment completion.…”
Section: Engagement Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the Roy et al study stated that facilitator attitudes, humanism, professionalism, and engagement in nondirective methods were most successful. Especially powerful were group leaders working as facilitators rather than experts (Roy et al, 2013). Of note is leaders serving as facilitator versus authority figures may more easily achieve successful recidivism reduction outcomes.…”
Section: Facilitator Educationmentioning
confidence: 99%
“…Kennealy et al (2012) posit that quality relationships reduce the risk of recidivism. Roy, Châteauvert, and Richard (2013) indicate that men who participate in IPV treatment emphasize the importance of their relationships with the groups' facilitators. Participants in the Roy et al study stated that facilitator attitudes, humanism, professionalism, and engagement in nondirective methods were most successful.…”
Section: Facilitator Educationmentioning
confidence: 99%